ANALISIS MANAJEMEN RISIKO PEMBIAYAAN MURABAHAH DI PT BPRS ARTHA MADANI KANTOR PUSAT BEKASI - Zahrina Wardatul Fawziyah; Isfandayani - (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2020)
Risk management is an important effort that must be made by Islamic Banking to minimize risk. This research is a qualitative research and the methods used are interviews, documentation, and observation. The research objective was to determine the types of risks in murabahah financing and the strategy of PT. BPRS Artha Madani in overcoming these risks and to find out the analysis of the implementation of risk management strategies carried out by PT. BPRS Artha Madani Head Office Bekasi.Based on the results of the study it is known that the risk management strategy analysis of PT. BPRS Artha Madani using Bank Indonesia Regulation No. 13/23/PBI/2011 and 5 C principles consist of Character, Capacity, Capital, Collateral and Condition of Economy. However, despite implementing the risk management strategy, banks continue to experience risks, namely in the form of: credit risk (in Islamic banks called as financing risk), operational risk and legal risk due to bank internal factors in analyzing and external factors from customers.PT. BPRS Artha Madani in resolving troubled financing with intensive billing, reprimand to customers if they do not fulfill their obligations, make a restructuring by rescheduling, reconditioning and restructuring if the financing can still be normalized. However, if there is no hope and the Customer is not able to, then the solution is guaranteed that can be auctioned through litigation or non-litigation channels.